JURIDICAL REVIEW SUSTAINABLE FOOD AGRICULTURAL LAND PROTECTION - Jenifer; Kartina Pakpahan; Jessica; Novi Yanti (Awang Long Law Review, 2022)
The purpose of this research is to analyze the occurrence of land conversion which is increasing from year to year from agricultural land to non-agricultural land. The research uses a normative juridical method which is carried out by examining literature studies and sources of this research using primary legal sources. The problem in this research is to analyze the policy of sustainable food agriculture land protection, the weaknesses of the policy and provide recommendations to improve these weaknesses. In Law No. 41 of 2009 article 28 discusses the development of agricultural technology that has not been evenly distributed and has not been kept up with the times. Education in agriculture is also still not in accordance with article 63. This land conversion occurs because there are fewer people who work as farmers and the lack of policies that support people to work as farmers. The area of ​​non-paddy agricultural land in 2019 was around 29,353,138 hectares and the area of ​​rice fields in 2019 was around 7,463,948 hectares. Indonesia should focus more on agriculture to overcome this land conversion.